2017
DOI: 10.1016/j.jseaes.2016.12.045
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary kinematics of the Ordos block, North China and its adjacent rift systems constrained by dense GPS observations

Abstract: The detailed kinematic pattern of the Ordos block, North China and its surrounding rift systems remains uncertain, mainly due to the low signal-to-noise ratio of the Global Positioning System (GPS) velocity data and the lack of GPS stations in this region. In this study, we have obtained a new and dense velocity field by processing GPS data primarily collected from the Crustal Motion Observation Network of China and from other GPS networks between 1998 and 2014. The GPS velocities within the Ordos block can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
38
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 38 publications
9
38
1
Order By: Relevance
“…This gives an average vertical slip rate of the HPF of ~0.24 mm/year during the late Pleistocene, equivalent to a horizontal extension rate of ~0.14 mm/year. Our Holocene result is comparable to the GPS‐derived extension rate of 0.5–1.0 mm/year (Middleton et al, ; Wang et al, ; Zhang et al, ; Zhao et al, ), but the average late Pleistocene rate is smaller than GPS‐derived results. The slip rate is comparable to the other major active faults and grabens around the Ordos; see Middleton et al ().…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This gives an average vertical slip rate of the HPF of ~0.24 mm/year during the late Pleistocene, equivalent to a horizontal extension rate of ~0.14 mm/year. Our Holocene result is comparable to the GPS‐derived extension rate of 0.5–1.0 mm/year (Middleton et al, ; Wang et al, ; Zhang et al, ; Zhao et al, ), but the average late Pleistocene rate is smaller than GPS‐derived results. The slip rate is comparable to the other major active faults and grabens around the Ordos; see Middleton et al ().…”
Section: Discussionsupporting
confidence: 84%
“…This gives an average vertical slip rate of the HPF of~0.24 mm/year during the late Pleistocene, equivalent to a horizontal extension rate of~0.14 mm/year. Our Holocene result is comparable to the GPS-derived extension rate of 0.5-1.0 mm/year (Middleton et al, 2017;Wang et al, 2001;Zhang et al, 2003;Zhao et al, 2017), but the…”
Section: Slip Parameters Of the Ce 1303 Eventsupporting
confidence: 89%
“…Furthermore, Li et al (2017) processed GPS data from a dense network of stations in the northeast Tibetan Plateau during 1999-2016 and found that the thrusting component of the Liupan Shan fault was approximately 2.9 ± 1.2 mm/a. Zhao et al (2017) suggested that shortening rate of the Liupan Shan fault was 3.0 ± 1.1 mm/a based on GPS data from 1998-2014. In this study, we assume that the shortening rate is identical to the movement velocity of the Liupan Shan, and the initial time of movement corresponds to the initial time of stage 3, which was 12 Ma (Li et al 2013).…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…Here, we suggest that there are two possible reasons for the normal faulting tectonic stress field in this area. One is that the Haiyuan and -Nivet et al, 2004;Qu et al, 2017;Wang et al, 2011Wang et al, , 2013Zhao et al, 2017), with this regulatory zone exhibiting a NNW-SSE extensional environment (Figure 11a). As the Liupanshan region is on the leading edge of the E-SE movement of the Liupanshan Basin secondary block and is in contact with other F I G U R E 9 (a) Results of crustal stress field inversion from the 240 fault plane solutions for the study area with a grid interval of 0.5 × 0.5 .…”
Section: Characteristics Of the Liupanshan Basin Stress Fieldmentioning
confidence: 99%